2016
DOI: 10.1097/01.sa.0000504626.99900.a9
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Two Multimodal Analgesic Techniques in Patients Predicted to Have Severe Pain After Cesarean Delivery

Abstract: BACKGROUND-Improved pain control after cesarean delivery remains a challenging objective. Poorly treated acute pain following delivery is associated with an increased risk of chronic pain and depression. This study was conducted to determine whether the addition of systemic acetaminophen and an increased dose of intrathecal morphine would further reduce acute pain. The primary outcome was pain intensity with movement at 24 hours postoperatively. Secondary measures included persistent pain and depression at 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…However, these studies did not stratify by individual patient requirements. An additional analgesia combination of acetaminophen plus a higher intrathecal morphine dose (300 μg vs 150 μg) has been used to good effect to women believed to be at higher risk of pain undergoing cesarean delivery 14. Studies applying gabapentin to unselected cohorts of women have found mixed results,15 16 and concerns for common side effects such as sedation have limited routine clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not stratify by individual patient requirements. An additional analgesia combination of acetaminophen plus a higher intrathecal morphine dose (300 μg vs 150 μg) has been used to good effect to women believed to be at higher risk of pain undergoing cesarean delivery 14. Studies applying gabapentin to unselected cohorts of women have found mixed results,15 16 and concerns for common side effects such as sedation have limited routine clinical use.…”
Section: Discussionmentioning
confidence: 99%